Методологічні аспекти дослідження правового регулювання - Тарахонич, Т.І. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Анализируется понятие методологии научного исследования, дается определение основных методов и приёмов, которые используются в процессе анализа правового регулирования и правового влияния как общетеоретических категорий. In the scientific article the concept of methodology of scientific research is analyzed, the analysis is given to the basic methods and receptions which are used in the course of the analysis of legal regulation and legal influence as general-theoretical categories.